Audyt zorientowany na kontrolę a audyt zorientowany na ryzyko - Bednarek, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper definition and history of internal auditing development. These general issues became a background for analyzing limitations of control-based auditing and some menaces when using the original COSO report as a framework. The main part of the article presents arguments for the need for opting for risk-based auditing and proposal of its model. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1178, s. 9-15